Cardiovascular and renal safety outcomes of hypoxia-inducible factor prolyl-hydroxylase inhibitor roxadustat for anemia patients with chronic kidney disease: a systematic review and meta-analysis - Lei Tian; Mengdi Wang; Mengchao Liu; Yanyu Pang; Jingwen Zhao; Bingjie Zheng; Yutong Wang; Wenjing Zhao (Renal Failure)
This systematic review and meta-analysis were conducted to evaluate the cardiac and kidney-related adverse effects of roxadustat for the treatment of anemia in CKD patients. 18 trials with a total of 8806 participants were identified for analysis. We employed a fixed-effects model for analysis. The pooled result revealed no significant difference in the risk of occurrence of cardiac disorders when comparing CKD patients receiving roxadustat with the placebo (RR = 1.049; CI [0.918 to 1.200]) or ESA (RR = 1.066; CI [0.919 to 1.235]), in both dialysis-dependent (DD) (RR = 1.094; CI [0.925 to 1.293]) or non-dialysis-dependent (NDD) (RR = 1.036; CI [0.916 to 1.171]) CKD patients. No significant difference was observed in the risk of kidney-related adverse events when comparing roxadustat with the placebo (RR = 1.088; CI [0.980 to 1.209]) or ESA (RR = 0.968; CI [0.831 to 1.152]), in DD (RR = 2.649; CI [0.201 to 34.981]) or NDD (RR = 1.053; CI [0.965 to 1.149]) CKD patients. A high risk of hyperkalemia was observed in the roxadustat group in DD (RR = 0.939; CI [0.898 to 0.981]). Incidence of hypertension was higher in the roxadustat for NDD patients (RR = 1.198; CI [1.042 to 1.377]), or compared to the placebo (RR = 1.374; CI [1.153 to 1.638]). In summary, the risk of cardiac or kidney-related events observed in the roxadustat was not significantly increase whether in DD or NDD patients. However, attention must be paid to the occurrence of hyperkalemia for DD patients and hypertension in NDD patients using roxadustat.